Parkinsonism and other movement disorders in outpatients in chronic use of cinnarizine and flunarizine Parkinsonismo e outros distúrbios do movimento em pacientes ambulatoriais sob uso crônico de cinarizina ou flunarizina - Giorgio Fabiani; Paulo C. Pastro; Carolina Froehner (Arquivos de Neuro-Psiquiatria)
The purpose of this study is to determine the prevalence and the patterns of movement disorders (MD) in outpatients submitted to the chronic use of cinnarizine (cz) or flunarizine (fz), and to establish the main risk factors for MD development. Over a period of 3 months, data were collected from outpatients who were chronic users of cz or fz in a municipal health institute. A total of 26 outpatients were included and all of them were submitted to a protocol that included DSM-4 diagnosis criteria for drug-induced movement disorders, parkinsonism (PK) and depression. Parkinsonism was diagnosed in 34% of the patients, PK plus akathisia, PK plus akathisia and bucco-linguo-masticatory syndrome (BLMS), isolated BLMS and dystonia were found in 4% patients each. Patients with BLMS had the highest median age and the longest average period in which they used the drugs. The affected group, when compared to the non-affected one, presented with higher rates of depression. This study demonstrates the existence of a direct relationship between the time of use of cz and fz, the age and the prevalence of PK and other MD. It also suggests that these drugs increase the incidence of depression. O objetivo deste estudo foi determinar a prevalência e os padrões de distúrbios do movimento (DM) em pacientes ambulatoriais sob uso crônico de cinarizina (cz) ou flunarizina (fz), além de estabelecer os principais fatores de risco para o seu aparecimento. Durante três meses foram coletados dados de pacientes ambulatoriais em uso de cz ou fz. Todos esses pacientes foram submetidos a protocolo pré-estabelecido que incluía critérios diagnósticos do DSM-IV para distúrbios do movimento induzido por drogas e critérios para diagnostico de depressão maior. Parkinsonismo (PK) puro foi diagnosticado em 34% dos pacientes, PK com acatisia, PK com acatisia e síndrome mastigatória bucolingual (SMBL), SMBL isoladamente e distonia, foram encontrados em 4% dos pacientes. Os pacientes com SMBL apresentavam a média de idade mais avançada, o maior tempo médio de uso das drogas, configurando-se o grupo de maior risco ao aparecimento dos DM. O grupo dos pacientes com DM apresentou maior incidência de depressão quando comparados com os não afetados. O estudo demonstra uma relação direta entre o tempo de uso da droga, a idade avançada do paciente e o surgimento dos DM. Os resultados também sugerem que estas drogas aumentam a incidência de depressão.